Pengaruh tanggung jawab sosial terhadap kinerja keuangan: Struktur kepemilikan sebagai variabel moderasi - Anita Anita; Desrika Putri Amalia (Jurnal Ekonomi Modernisasi, 2021)
This research was conducted to prove empirically the influence of social responsibility on financial performance moderated by the ownership structure of companies listed on the Indonesia Stock Exchange. The variables contained in this study were ownership concentration, the proportion of tradeable shares, leverage, long-term debt, and company size. The proportion of tradeable shares and ownership concentration were moderating variables. Companies listed on the Indonesia Stock Exchange with a total sample of 384 companies were selected based on predetermined criteria. Eviews were programs used to test panel data taken from annual company reports published for 5 years. The results of the study after the data test stated that social responsibility has a significant positive effect while the proportion of tradeable shares and ownership concentration do not have a significant effect on performance. The moderating variables contained in this study positively influence corporate social responsibility toward financial performance.